Education and science: current trends - Bodrov A. G., Nikishina A. A., Novikov I. A., Novikov A. P., Surkova G. V., Petrova D. D., Samostroenko G. M., Shatokhina O. V., Cherkashin I. S., Kapustina N. V., Rustamova I. T., Savenkov D. L., Veselova N. I., Grigorian S. S., Milioshina N. A., Firsova I. A., Chibilyova V. P., Chibiliov A. A., Sagitova V. R., Borovkova V. A., Borovkova V. A., Shevtsov V. V., Efremov A. Y., Diakieva B. B., Averianova E. V., Belonovskaia I. D., Sorokina O. A., Rakhimova O. N., Emelianova E. V., Chereshneva I. E., Kokhanova L. A., Golovko S. B., Khokhrina I. S., Khachev M. M., Temmoeva S. A., Cherkasova O. A., Zakirov R. S., Belousova rimma iurevna R. I., Novoselova A. N., Podoplelova N. M., Danilchenko S. L., Boldyrikhina V. N. (Education and science: current trends, 2018)
in modern conditions, the role of intellectual capital increases. Personal and collective intelligence become the determining factors of strategic development of the educational organization. This, in turn, requires strategic development of intellectual capital. The work deals with the components and content of the process of such development. The concept of educational intellectual capital is given and it is shown that the strategic development of educational intellectual capital should provide the necessary compliance and understanding of the external environment. Types of educational institutions are selected, different in strategic orientation for the development of their educational and intellectual capital.
Keywords: образовательный интеллектуальный капитал; стратегическое развитие; стратегические соответствия; интеллектуальные дефициты; обучающаяся организация; educational intellectual capital; strategic development; strategic compliance; intellectual deficits; learning organization